Combustion possibility assessment for separating launch-vehicle components during atmospheric phase of descent trajectory. (June 2019) - Trushlyakov, V.; Zharikov, K.; Davydovich, D.
Abstract: The investigation is made of the processes associated with the combustion of separating launch vehicle components (LVCs) on the atmospheric phase of the descent trajectory. This allows us to provide a radical solution to the problem of reducing the areas of the LVC impact zones. Ballistic parameters values for the LVC motion are determined. Such areas are proposed for realizing LVC heating to the ignition temperature through the energy mixture burning. Further combustion of the LVC occurs when there is a sufficient amount of oxygen in the oncoming air stream. Highlights: LVC heating to the ignition temperature by supplying additional heat. The possibility of using energy materials to produce heat. The fields of ballistic movement parameters well-suited for the proposed implementation of the heat.